First results of HF radio science with e‐POP RRI and SuperDARN. Issue 1 (20th January 2017) - Perry, G. W.; James, H. G.; Gillies, R. G.; Howarth, A.; Hussey, G. C.; McWilliams, K. A.; White, A.; Yau, A. W.
Abstract: The first results from coordinated experiments between the Radio Receiver Instrument (RRI) on the Enhanced Polar Outflow Probe (e‐POP) and the Super Dual Auroral Radar Network (SuperDARN) Saskatoon high frequency (HF) radar are examined for a conjunction on 8 July 2014. e‐POP, a payload on the CAScade, Smallsat and IOnospheric Polar Explorer spacecraft, was located at 380 km altitude, approximately 10° north (geographic) and 2° west of Saskatoon, Canada, moving in a southeast direction. We use a matched filter technique to extract individual received SuperDARN pulses from the RRI data stream. The pulses show characteristics of propagation through the F region ionosphere: they are heavily dispersed, they show significant pulse‐to‐pulse variability in magnitude, and there is clear evidence that they experienced multipath propagation. We calculate the polarization parameters of the pulses and use them to identify magnetoionic phenomena such as mode‐splitting and single‐mode fading. These first RRI results provide compelling insight into HF radio wave propagation and show RRI's potential to significantly advance radio science. Key Points: e‐POP RRI is an effective tool for detecting radar pulses and studying HF radio wave propagation in the ionosphere HF radar pulses detected by e‐POP RRI are significantly dispersed and split into O ‐ and X ‐mode components. Single‐mode fades also detected Multipath propagation between transmitting radar and e‐POP RRI was detected and identified as coherent backscatter